Offshore Antarctic Peninsula Gas Hydrate Reservoir Characterization by Geophysical Data Analysis - Maria Filomena Loreto; Umberta Tinivella; Flavio Accaino; Michela Giustiniani (Energies, 2010)
A gas hydrate reservoir, identified by the presence of the bottom simulating reflector, is located offshore of the Antarctic Peninsula. The analysis of geophysical dataset acquired during three geophysical cruises allowed us to characterize this reservoir. 2D velocity fields were obtained by using the output of the pre-stack depth migration iteratively. Gas hydrate amount was estimated by seismic velocity, using the modified Biot-Geerstma-Smit theory. The total volume of gas hydrate estimated, in an area of about 600 km2, is in a range of 16 × 109–20 × 109 m3. Assuming that 1 m3 of gas hydrate corresponds to 140 m3 of free gas in standard conditions, the reservoir could contain a total volume that ranges from 1.68 to 2.8 × 1012 m3 of free gas. The interpretation of the pre-stack depth migrated sections and the high resolution morpho-bathymetry image allowed us to define a structural model of the area. Two main fault systems, characterized by left transtensive and compressive movement, are recognized, which interact with a minor transtensive fault system. The regional geothermal gradient (about 37.5 °C/km), increasing close to a mud volcano likely due to fluid-upwelling, was estimated through the depth of the bottom simulating reflector by seismic data.